THE ART OF R PROGRAMMING - MATLOFF NORMAN (CALIFORNIA NO SCRATCH PRESS INC, 2011)
The Art of R Programming by Norman Matloff is a comprehensive guide to programming with R, focusing on software development rather than just statistical analysis. It covers basic types and data structures like vectors, matrices, arrays, lists, and data frames, and advances to programming constructs such as flow control, functions, and simulations. The book also delves into object-oriented programming in R, string manipulation, and graphics.
R PROGRAMMING
COMPUTERS
Keywords: STATISTICS; COMPUTER PROGRAM LANGUAGE